Miradas sobre el matrimonio en la España del último tercio del siglo XVIII - Chacón Jiménez, Francisco; Méndez Vázquez, Josefina (Cuadernos de Historia Moderna, 2007)
The evolution of the marriage, it has generated temporary models according to the ideology of each time. This way, the pattern of marriage of free election or for love, with their secret connections without the paternal consent, it is rejected by the absolutism that, with the acquiescence of the Church, she tries to impede the unequal unions by means of the promulgation of the Pragmatic Sanction of 1776. At the end of the XVIII century the strategic net of the advantageous marriage you fissure because of the unions free of family pacts; and, consequently, be initiated the gestation a new model matrimonial precursor of the romantic nineteenth, like a breaker vindication of the social class order. The other looks will contemplate the speech matrimonial at the end of century of the Church and analysis in the illustrated matrimonial pattern from a manly perspective.